The Role of Digital Zakat Transformation in Increasing Muzaki Participation and Expanding the Impact of Zakat Distribution in Indonesia - Ulfatul Ma'lufah; Muhammad Hasbi Zaenal (International Journal of Zakat, 2026)
PurposeThis study examines how digital transformation in zakat management enhances muzaki participation and strengthens the efficiency, transparency, and social impact of zakat distribution in Indonesia, with particular attention to alignment with Sustainable Development Goals (SDGs). Design/Methodology/ApproachThis descriptive qualitative research analyzes institutional reports from BAZNAS, Dompet Dhuafa, and Rumah Zakat (2019-2024), PUSKAS BAZNAS publications, and peer-reviewed literature on digital zakat. Twenty-three documents were systematically reviewed using qualitative content analysis involving data reduction, categorization, and thematic interpretation to identify patterns in digital transformation impacts. FindingsDigital zakat platforms significantly increased muzaki participation, particularly among millennials and urban communities, with national collection growing from IDR 10.2 trillion (2019) to IDR 18.9 trillion (2024). Mobile applications, real-time dashboards, and blockchain systems enhanced the transparency and operational efficiency by 40%, while AI-based mustahik mapping improved targeting accuracy by 70%. Approximately 78% of muzaki expressed greater trust in institutions providing digital reporting. However, the digital divide, literacy gaps, and cybersecurity concerns remain significant barriers. Research limitations/implicationsReliance on secondary institutional data limits generalizability. Future research should incorporate empirical surveys and cost-benefit analyses of emerging technologies. Practical implicationsZakat institutions should prioritize integrated national platforms, digital literacy programs, and cybersecurity frameworks to optimize collection and distribution while ensuring inclusive access. Social implicationsDigital zakat promotes financial inclusion, increases social trust in Islamic philanthropic institutions, and broadens access to socio-economic assistance especially in remote or underserved communities. Originality/valueThis study provides comprehensive synthesis of Indonesia's digital zakat ecosystem, demonstrating how technological innovation reshapes Islamic philanthropic governance as a strategic instrument for inclusive development aligned with maqashid shariah principles.